Memory and metamemory for semantic information in obsessive-compulsive disorder - TOPÇUOĞLU, VOLKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Several studies have been conducted on OCD patients' memory and metamemory performance in episodic tasks. However, there is a clear lack of research addressing these issues for semantic memory (i.e., retrieval of information from long-term memory). Although findings regarding a memory deficit is somewhat equivocal, the empirical evidence clearly demonstrates that OCD patients with primarily checking compulsions show reduced confidence in their memory performance. The purpose of the present study was to investigate memory and metamemory performance of checkers in semantic memory domain. We compared checker OCD patients, non-checker OCD patients and normal controls on their ability to retrieve answers to general knowledge questions with a recall as well as a recognition test. We also investigated prospective (feeling-of-knowing (FOK)) and retrospective (confidence) metamemory judgments. Checker OCs were not poorer in retrieving semantic information from long-term memory. Neither were they less confident about their ability to remember currently unrecallable information in the future (FOK judgments) or about the accuracy of retrieved information (confidence judgments). Moreover, accuracy of metamemory judgments were comparable across groups. Overall, our results revealed that checker OCs do not show a memory or metamemory deficit when semantic memory was concerned, suggesting that any memory and metamemory deficit may be special to recently experienced materials. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: obsessive-compulsive disorder; memory; metamemory; feeling of knowing; semantic memory; confidence; CHECKERS; SCALE; CONFIDENCE; ACCURACY; DEFICITS; WORRY